Optimizing Bioky Performance Using Super Small Vessel in Wastewater Treatment Installation at PT. X in Klaten - Waluyo, Joko; paryanto, paryanto; Alamsyah, Raihan; Kurniawan, Deni; Pranoto, Ibnu Singgih; Cahyani, Yulinar Pramesti (Program studi Teknik Kimia UNS, 2024)
One of the causes of environmental pollution is liquid waste generated by industries, especially the printing industry. PT Macanan Jaya Cemerlang is one of the printing industries producing liquid waste that does not meet the quality standards. The purpose of this research is to optimize the performance of Bioky bacteria using the Super Small Vessel in the wastewater treatment plant at PT X Klaten. Treatment involves testing variables such as residence time and bacteria quantity's impact on TSS, MBAS, COD, BOD, pH, and ORP.The study employs anaerobic treatment with observed variables: residence time of 1; 2; and 3 days, and bacteria quantity of 2.4; 3.2; and 4 liters. Samples from each variable are then analyzed for pH, ORP, and TSS. COD, BOD, and MBAS are tested after obtaining the best TSS results from each variable.The research results indicate that longer residence time and increased bacteria quantity lead to greater reduction in TSS, COD, BOD, and MBAS, while pH approaches neutrality. Optimal conditions occur at a 3-day residence time with 4,0 liters of bacteria, resulting in a reduction of TSS, COD, BOD, and MBAS against the inlet by 99.75%, 95.47%, 94.84%, and 26.72%. Although the treated waste doesn't meet the established standards, it effectively reduces the pollution levels in PT X's wastewater. Keywords:Anaerobic, Efficiency, Printing Industry Liquid Waste, Super Small Vessel